NONMETRIC EXAMINATION OF PALEOANTHROPOLOGICAL FINDINGS FROM EASTERN MONGOLIA, 2003 - M.ERDENE (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2023)
In this paper, we present the results of cranial nonmetric examination of paleoanthropological findings discovered during archaeological excavations in Eastern Mongolia in 2003. The 18 more or less well preserved skulls were studied for the presence or absence of 81 nonmetric cranial traits from which 55 were observed in the sample, considerably varying in frequencies of their occurrence. The observed frequencies and percentages of the traits are compared to those of Siberian, Far East Asian and Circum Pacific region populations. The nonmetric examination of the series suggest that ancient populations from Eastern Mongolia, specially, the population from Tahilgat, Tsuvraa and Sant sites, Khulenbuir sum, Dornod aimag is very distinct in their biological features expressed by some specific nonmetric cranial traits.